The Relationship between Parents' Learning Motivation and Socio-Economic Status with Science Learning Achievement - Krido Bangun Nugroho, Dwi Kodrat; Raharjo, Tri Joko; Utomo, Udi (Universitas Negeri Semarang, 2020)
Motivation has a strategic role in one's learning activities; besides, parents' socio-economic conditions also affect the educational process. This study aimed to find out the relationship between learning motivation and socio-economic status of parents with science learning achievement. This research used post facto method with a quantitative research design. The research data from 85 students was taken using questionnaires and tests. Testing the instrument was done by testing the validity and reliability testing. The data analysis technique used descriptive analysis, analysis prerequisite test, hypothesis testing. The results showed a relationship between learning motivation and parents’ socio-economic status that affected science learning achievement. The results of the linearity test showed that the learning motivation Fcount was 0.664 > 0.05, the economic status of the parents was 0.977 > 0.05, so the learning motivation and economic status of the parents towards learning achievement were linear. The results of hypothesis testing using the t test obtained t count of 4,875 and t table of 1,988, then t count > t table. It can be concluded that partially the motivation to learn and parents' socio-economic status has a strong relationship with science learning achievement.